2015
DOI: 10.1177/0363546515597486
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoparalysis From a Massive Rotator Cuff Tear Is Reliably Reversed With an Arthroscopic Rotator Cuff Repair in Patients Without Preoperative Glenohumeral Arthritis

Abstract: ARCR can lead to reversal of preoperative pseudoparalysis in patients with minimal preoperative glenohumeral arthritis. ARCR is a viable first line of treatment for patients with pseudoparalysis in the absence of advanced glenohumeral arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 33 publications
2
48
0
1
Order By: Relevance
“…The repair or partial repair of MRCT leads to pain reduction in over 80% of the patients [ 2 , 5 ]. Even a high rate of reversion of pseudoparalysis for repairs of MRCT in the absence of osteoarthritis has been described [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The repair or partial repair of MRCT leads to pain reduction in over 80% of the patients [ 2 , 5 ]. Even a high rate of reversion of pseudoparalysis for repairs of MRCT in the absence of osteoarthritis has been described [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that massive cuff tears are usually completely reparable, 2 and that even in patients with massive tears associated with pseudoparalysis, the pseudoparalysis is reversible in >90% of cases after cuff repair. 1 However, we freely admit that some tears are not fully reparable. In such cases, the surgical choices are partial cuff repair versus rTSA.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The vast majority of massive tears have been fully reparable in our hands. In the small percentage of tears that have not been fully reparable, we have done partial repairs.…”
mentioning
confidence: 99%
“…The most common definition is less than 90 of active shoulder elevation. [8][9][10] However, this definition includes limited active elevation due to shoulder pain. In our previous publication addressing pseudoparalysis with fascia lata autograft SCR, we divided pseudoparalysis into 2 subgroups: (1) moderate pseudoparalysis, that is, no shoulder stiffness, less than 90 of active shoulder elevation, and the ability of patients to maintain more than 90 of elevation once the shoulder is elevated passively, and (2) severe pseudoparalysis, that is, no shoulder stiffness, less than 90 of active shoulder elevation, and the presence of a positive drop-arm sign (patients cannot maintain the abducted position because of muscle weakness).…”
Section: See Related Article On Page 22mentioning
confidence: 99%